PENGARUH KEPEMIMPINAN DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN PT. SUZUKI FINANCE INDONESIA PALU - Muhlis, Muhlis (Katalogis, 2016)
The aims of this research are : 1) to find out and analyze the simultaneous influence of leadership and career development on employee’s performance at PT. Suzuki Finance Indonesia Palu ; 2) to find out and analyze the influence of leadership on employee’s performance at PT. Suzuki Finance Indonesia Palu ; 3 ) to find out and analyze the influence of career development on employee’s performance at PT Suzuki Finance Indonesia Palu. This research is descriptive that explains the influence of leadership and career development on employee’s at PT. Suzuki Finance Indonesia Palu with 39 respondents who are selected through purposive sampling method. The results show that: 1) leadership and career development simultaneously have significand and positive influence on employee’s performance at PT Suzuki Finance Indonesia Palu ; 2 ) leadershif partially has positive and significant influence on employee’s performance at PT. Suzuki Finance Indonesia Palu ; 3 ) career development partially has positive and significant influence on employee’s performance at PT. Suzuki Finance Indonesia Palu.